PERLINDUNGAN HUKUM BAGI KREDITUR TERHADAP EKSEKUSI JAMINAN ATAS TANAH HAK MILIK YANG BERADA DALAM KAWASAN HUTAN DI DAERAH KABUPATEN PADANG LAWAS UTARA - PEBRI YANTI SIREGAR (PREMISE LAW JURNAL, 2015)
Both the Land Office and the Forestry Service have authority to handle land administration. This type of authority which exists in every region has brought about conflict which has an effect on the process of regional economic development such as what happens in Padang Lawas Utara District. A claim on a tract of land by the Forestry Service consider that it is a forest area, based on the Decree of the Minister of Forestry No. 44/Menhut-II/2005 on the Indication of Forest Area in North Sumatera Province in the area of ± 3,742,120 hectares. Along with that, the Land Office also has the right to do land administration, based on the Government Regulation No. 24/1997 on Land Registration. In 2007, Land Certificate was issued in Padang Lawas Utara District. According to SK No.24/Menhut-II/2005, the land was located in forest area. In 2012, the certificate became the collateral in PT. Bank Sumut, Gunungtua Branch. Keywords: Legal Protection, Creditor, Forest Area